2000
DOI: 10.1074/jbc.m002629200
|View full text |Cite
|
Sign up to set email alerts
|

Expression Cloning of a New Member of the ABO Blood Group Glycosyltransferases, iGb3 Synthase, That Directs the Synthesis of Isoglobo-glycosphingolipids

Abstract: The large array of different glycolipids described in mammalian tissues is a reflection, in part, of diverse glycosyltransferase expression. Herein, we describe the cloning of a UDP-galactose: beta-d-galactosyl-1,4-glucosylceramide alpha-1, 3-galactosyltransferase (iGb(3) synthase) from a rat placental cDNA expression library. iGb(3) synthase acts on lactosylceramide, LacCer (Galbeta1,4Glcbeta1Cer) to form iGb(3) (Galalpha1,3Galbeta1, 4Glcbeta1Cer) initiating the synthesis of the isoglobo-series of glycosphing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
95
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 32 publications
1
95
0
Order By: Relevance
“…The human genome encodes more than 200 different glycosyltransferases, and the field of glycodiversification is constantly expanding with both in vitro synthesis and modifications of natural glycoconjugates used in pharmaceuticals for example (2). However, glycosyltransferases appear to be more promiscuous than previously believed as they are able to use different donor and acceptor molecules (3).…”
mentioning
confidence: 86%
“…The human genome encodes more than 200 different glycosyltransferases, and the field of glycodiversification is constantly expanding with both in vitro synthesis and modifications of natural glycoconjugates used in pharmaceuticals for example (2). However, glycosyltransferases appear to be more promiscuous than previously believed as they are able to use different donor and acceptor molecules (3).…”
mentioning
confidence: 86%
“…Importantly, while the use of animals deficient in the ␣1,3-galactosyltransferase may appear to be the most attractive option for animal to human xenotransplantation, studies have suggested that some tissues, including the vascular endothelium of deficient animals, may in fact still express minor quantities of Gal␣1-3Gal epitopes (41,42). The most likely explanation for this has been identified as expression of the isogloboside glycolipid (Gal␣1-3Gal␤1-4Glc␤1-Cer) (42), which is controlled by another homologous glycosyltransferase of the CAZy GT6 family, the iGb3 synthase (UDP-Gal:lactosylceramide ␣1,3-galactosyltransferase) (43).…”
Section: Discussionmentioning
confidence: 99%
“…Most GT-A fold GTs, including those in the GT6 family, require divalent metal ions, such as Mn 2ϩ , for catalytic activity; their metal dependence is linked to a shared DXD sequence motif. Residues of this motif interact with the metal ion and both the ribose and phosphates of the donor substrate to produce an appropriate substrate orientation and conformation for catalysis and to stabilize the UDP leaving group (3,(7)(8)(9)(10).Mammalian members of GT6 are responsible for variations in glycan structures between different species and individuals as the result of selective enzyme inactivation in certain species (␣3GT, Forssman glycolipid synthase, and isogloboside 3 synthase) or the inheritance of multiple alleles at one locus that encode enzymes with different substrate specificity (GTA and GTB) or are inactive (11)(12)(13)(14). The presence of circulating antibodies against glycan structures that are subject to interspecies and individual variability has been linked to resistance to pathogens that also carry the glycans; these antibodies are thought to arise from exposure to potential pathogens, including enveloped viruses and bacteria that carry structurally similar glycans (11).…”
mentioning
confidence: 99%
“…Mammalian members of GT6 are responsible for variations in glycan structures between different species and individuals as the result of selective enzyme inactivation in certain species (␣3GT, Forssman glycolipid synthase, and isogloboside 3 synthase) or the inheritance of multiple alleles at one locus that encode enzymes with different substrate specificity (GTA and GTB) or are inactive (11)(12)(13)(14). The presence of circulating antibodies against glycan structures that are subject to interspecies and individual variability has been linked to resistance to pathogens that also carry the glycans; these antibodies are thought to arise from exposure to potential pathogens, including enveloped viruses and bacteria that carry structurally similar glycans (11).…”
mentioning
confidence: 99%